Kajian Etnobotani Tumbuhan Ritual dalam Tradisi Kenduren Jagad : Eksplorasi Kearifan Lokal Masyarakat Andonosari, Pasuruan - Syvangi Dwi Pramudya; Evi Sintia Nuramalia; Johanna Kartika Adventina P. Dasuha; Fahrul Ghani Muhaimin; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study examines the use of plants in the Kenduren Jagad tradition in Andonosari Village, Pasuruan Regency as a form of community ethnobotanical practice. The method used is descriptive qualitative through interviews, observation, and documentation, with the determination of informants by purposive and snowball sampling and interactive model data analysis. The results of the study identified 23 plant species from 14 families, with a dominant herbaceous habitus (52%) compared to shrubs (48%). The use of plants is divided into three main patterns, namely as tumpeng food ingredients, ancak decorations, and symbolic in ritual processions. Plants used as food ingredients include broccoli, bean sprouts, and carrots, while most other types are used as ancak decorations to beautify the ritual appearance based on variations in shape and color. Symbolically, plants represent the values ​​of gratitude, prosperity, and balance in community life. Plant parts used include flowers, fruits, leaves, tubers, seeds, and pods, with the dominance of fruit and leaf organs. All plants are obtained through local cultivation with a relatively safe conservation status (least concern and not evaluated), so as not to put pressure on wild natural resources. This pattern demonstrates the close relationship between cultural practices and locally based biological resource management. Thus, the Kenduren Jagad tradition serves as a model for biocultural conservation that not only preserves biodiversity but also maintains the sustainability of the community's ethnobotanical knowledge.